PENGARUH TEKNIK REFRAMING UNTUK MENGURANGI KECEMASAN SOSIAL SISWA MELALUI BIMBINGAN KELOMPOK DI SMP NEGERI 34 PEKANBARU - Manalu, Sondang Trinora; Arlizon, Raja; Putra, Roby Maiva (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Social anxiety is an excessive feeling of worry when an individual is in a social situation such as worrying about getting a negative judgment from another person, nervousness, shame, rejection, lack of confidence, discomfort and tend to avoid social activities. Of course these anxiety feelings interfere with the learning process of students in the implementation of tasks and social activities where social anxiety will affect emotional and cognitive conditions. One way to reduce social anxiety is to use Reframing techniques. The purpose of this study was to describe students' social anxiety before and after being given Reframing techniques through group guidance, to determine differences in students' social anxiety before and after being given Reframing techniques through group guidance and to determine the effect of Reframing techniques through group guidance on decreasing students' social anxiety. This research is an experimental quantitative study with the approach of one group pre-test and post-test The results showed that: (1) Social anxiety of students before being given a Reframing technique through group guidance is mostly in the high category, student learning anxiety after being given a Reframing technique through group guidance is mostly in the medium category. (2) There are differences in students 'social anxiety before and after being given a Reframing technique through group guidance which shows a decrease in students' social anxiety. (3) There is a significant effect of Reframing techniques on students' social anxiety through group guidanceKey Words: Reframing Technique, Social Anxiety